"The whole perimeter is difficult": Parkinson's disease and the conscious experience of walking in everyday environments. Issue 23 (6th November 2019) - Parry, Ross; Buttelli, Olivier; Riff, Jacques; Sellam, Narjis; Vidailhet, Marie; Welter, Marie-Laure; Lalo, Elodie
Abstract: Purpose: This study sought to characterize the way patients with Parkinson's disease consciously perceive and respond to their surroundings while walking in everyday situations. Method: A qualitative research program designed around an ecological data collection protocol was employed. A convenience sample of 14 patients with a diagnosis of Parkinson's disease and a history of gait difficulties were recruited. Details regarding patients' subjective experience of walking in everyday environments were obtained using first person interviewing techniques with the support of video footage from their daily-life activity. Interview transcripts were analyzed using an interpretive phenomenological approach in order to derive key themes. Results: The sense of proximity and the way in which an individual perceived themselves with respect to their surroundings appeared central to the way patients organized their locomotor behavior. Further to this, the patient relationship to different features and obstacles appeared conditioned by prior experiences in those circumstances. Patients described managing gait difficulties by consciously regulating their walking trajectory and gaze with respect to their environment. Conclusion: Perceptual challenges, visual flow and the dynamic valence of features in the patient's surroundings may have important effects upon the gait stability of patients with Parkinson's disease and warrant further attention in planning rehabilitation interventions. Implications for rehabilitation: Walking abilities of patients with Parkinson's disease should be conceptualized in terms of perceptuomotor coupling to a given environment. The functional significance of a patient's environment is dynamic and might be seen to vary in accordance with their physical capacities. Valency, or the subjective relationship between a patient and their surrounds, appears to be an important component of the "fit" between a person and their environment. Novel rehabilitation strategies for the management of parkinsonian gait disturbances might seek to integrate psychological, sensorimotor and environmental elements in order to have individually tailored, ecologically valid home assessment and community rehabilitation programs.